Analisis Pengaruh Modernisasi Terhadap Perkembangan Ekonomi Pada UMKM Makanan Viral Wonton - Fiky Binti Zakiyah; Madia Mutiara Andini; Lyca Shelya Dewi (Jurnal Riset Ekonomi dan Akuntansi, 2024)
Modernization is the process of transforming traditional community life into modern life. Technological developments caused by modernization have a significant impact on human survival, especially on the phenomenon of the influence of modernization on economic development. This research analyzes and explores the influence of modernization on economic development in MSMEs of viral wonton food. Modernization in this context includes the use of digital technology, product innovation and modern marketing strategies. The results of this research show that the application of digital technology such as social media significantly increases product visibility and sales. Innovations in flavors and packaging also attract the attention of new consumers and retain customers. The development of technology due to modernization provides opportunities for MSMEs to innovate in their business activities. This research uses a qualitative method with a phenomological approach. the data collection techniques used in this research were observation, interviews and documentation.